An Analysis of Translation Techniques in translating Enola's Utterances in Enola Holmes Movie - Putra, Dhanu Ario; Nopriansah, Nopriansah; Ependi, Selviyan; Mutmainah, Yeni (UNIVED Press, Universitas Dehasen Bengkulu, 2020)
Translation nowadays can generally be understood as an effort to transfer the source language to the target language. expert states that in the field of languages, translation today has several meanings, namely first is the general subject field or phenomenon, second is the product that is the text that has been translated, third is the process of producing the translation, otherwise known as translating. In terms of the translation itself, researchers can pay more attention to translation products where translator translates by reading the entire text and translating the source language into the target language. This research aims to describe the translation techniques used by HaiBunda.com in translating the English movie entitled